2012
DOI: 10.1080/01154451.2012.734094
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in democracy: Insights from an empirical analysis of political dynasties in the 15th Philippine Congress

Abstract: This paper presents metrics to estimate the size of political dynasties in the 15th Congress of the Republic of the Philippines and analyze the relationship between political dynasty and socio-economic outcomes.Results show that political dynasties comprise 70 percent of jurisdiction-based legislators in the current Congress. They possess higher net worth and win elections by larger margins of victory compared to not political dynasties. Jurisdictions of political dynasties are characterized by lower standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 19 publications
2
30
0
4
Order By: Relevance
“…Dal Bo et al 2009). Furthermore, Mendoza, et al (2012) found evidence that political dynasties in the 15th Congress won by much larger margins of victory, and tended to be wealthier. Nevertheless, they found that Philippine provinces with higher levels of political dynasties also displayed higher levels of poverty and weaker indicators of human development.…”
Section: Self-perpetuationmentioning
confidence: 99%
See 3 more Smart Citations
“…Dal Bo et al 2009). Furthermore, Mendoza, et al (2012) found evidence that political dynasties in the 15th Congress won by much larger margins of victory, and tended to be wealthier. Nevertheless, they found that Philippine provinces with higher levels of political dynasties also displayed higher levels of poverty and weaker indicators of human development.…”
Section: Self-perpetuationmentioning
confidence: 99%
“…His analysis of the disbursement of the constituent development fund (CDF) of legislators tends to favor local patrons, particularly mayoral partisan allies in their districts. Such a skewed allocation of resources could also potentially weaken the chances to attain policy objectives such as poverty reduction, as argued by Mendoza, et al (2012). Hence, self-perpetuation and (less robust) poverty reduction outcomes may actually be linked, even as it appears that political patrons are trying to spend public funds in a "pro-poor" way.…”
Section: Self-perpetuationmentioning
confidence: 99%
See 2 more Smart Citations
“…The role that elites and well‐entrenched families play in politics, no doubt, has long captured the interest of scholars of Philippine politics who sought to explain whether the persistence of political dynasties has contributed to lagging economic outcomes and democratic capture (Mendoza, Beja, Venida, & Yap, ; Rivera, ). Mendoza, Beja, Venida, and Yap () believe there is strong evidence that political dynasties proliferate in the most economically depressed provinces but admit that political dynasties may not necessarily be inducing poverty.…”
mentioning
confidence: 99%